COMPARISON OF PREDICTIVE ACCURACY OF TANAKA-JOHNSTON ANALYSIS, MELGACO FORMULA AND BHERWANI’S REGRESSION EQUATION FOR PATIENTS PRESENTING TO ARMED FORCES INSTITUTE OF DENTISTRY - Akhtar, Faheem Nake; Tariq, Sana; Jan, Abdullah; Amin, Erum; Bangash, Azhar Ali; Khan, Mehwish (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare Tanaka-Johnston Mixed Dentition Analyses, Melgaco’s Formula and Bherwani’s Regression Equation in predicting the widths of mandibular canine and premolars, in a population presenting to AFID.Study Design: Cross-sectional Analytical Study.Place and Duration of Study: Department of Orthodontics, Armed Forces Institute of Dentistry Rawalpindi, from Aug 2018 to Jul 2019.Methodology: According to selection criteria, 200 subjects presenting to AFID were selected through non-probability consecutive method. Study models were poured and mesiodistal widths of mandibular incisors, canines, premolars and molars were measured. The results were compared with predicted width values obtained from Tanaka Johnston Analysis, Melgaco Formula, and Bherwani’s Regression Equations and analyzed using paired sample t tests. Results: There was a significant difference between actual and predicted widths of lower canines and premolars for all three methods; Tanaka Jhonston Analysis (p